Seven o'Clock Tales - Enid Blyton (London, United Kingdom Egmont UK Ltd, 2002)
Meet the mischievous shoemaker who sews a Skippety Spell into the King's shoes; a pixie who finds a shoelace which grants his every wish; and a basketful of brownies on their way to a pary in Fairyland.
Keywords: Fiction -- Fiction